Dwudziestolecie Zakładu i Katedry Historii Wychowania w Uniwersytecie Szczecińskim (1992–2012) - Jankowski, Robert (Biuletyn Historii Wychowania, 2013)
The History of Education, one of the courses offered at teacher education studies at the University of Szczecin, has been taught since the 1960’s. It was then when Teacher Education College in Szczecin was set up as a branch of Adam Mickiewicz University, Poznań. In 1973 Teacher Education College was transformed into an independent unit – Pedagogy Academy. The establishment of the University of Szczecin in 1985 marked a new chapter in the process of the development of the history of education as a course offered at pedagogical studies. History of Education Department was set up in 1992 and professor Danuta Koźmian was chair of the department throughout its existence. Scientific and didactic work of professor Danuta Koźmian first at Teacher Education College, through Pedagogy Academy and the University of Szczecin has been crucial for the development of the history of education as a course taught at teacher education studies in Szczecin. In 2008 professor Danuta Koźmian retired and the Council of the Faculty of Humanities at the University of Szczecin established the Chair for the History of Education appointing professor Wiesław Andrukowicz, Ph.D its head.